Can Sterilized FX Purchases under Inflation Targeting be Expansionary? - Márcio G. P. Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2011)
Unlike common wisdom, sterilized FX purchases under inflation targeting, i.e., those that keep the interest rate at the level targeted by the central bank, generally increase aggregate demand. We resort to a simple model with a credit channel to argue that FX purchases, by funding bank credit, end up increasing aggregate and money demand, while expanding loans and reducing the loan interest rate. Therefore, restoring the interest rate to the level previous to the FX purchase may not be sufficient to avoid the expansionary effect; the new money market equilibrium, at the same interest rate, will entail a larger money supply, higher output and larger money demand. Recent Brazilian evidence is reviewed, showing that this effect may be empirically relevant. If this is the case, inflation targeters may have another reason to be concerned when conducting FX sterilized interventions, besides their high cost and controversial effectiveness in preventing nominal appreciation. FX sterilized purchases may not only fail to prevent nominal appreciation, but also boost activity and inflation, thereby appreciating the real exchange rate.
Keywords: F3; F4; E5; 330; Devisenmarkt; Wechselkurspolitik; Inflationssteuerung; Brasilien; Kapitalmobilität; Inflationssteuerung; Brasilien